Multilevel noncontiguous cervical spine injury - Adetunji Mapaderun Toluse (Journal of Clinical Sciences, 2017)
This case report highlights the successful combination of operative and nonoperative management of a patient with noncontiguous cervical spine fractures and incomplete spinal cord injury. A case report of a 40-year-old male victim of a motor vehicular accident who presented with noncontiguous cervical spine fractures (Anderson and D'Alonzo Type III odontoid fracture and traumatic spondylolisthesis of C4/C5) and incomplete spinal cord injury. The odontoid fracture was managed nonoperatively, whereas anterior cervical discectomy and fusion were done at the C4/C5 vertebral level. The patient made full neurologic recovery with radiologic evidence of successful fusion and fracture healing at 12 weeks postoperation in both levels of injuries. Operative and nonoperative modalities can be utilized to manage selected patients.